Are age‐related differences in the consequence of work injury greater when occupational physical demands are high?. Issue 4 (24th January 2014) - Smith, Peter; Bielecky, Amber; Koehoorn, Mieke; Beaton, Dorcas; Ibrahim, Selahadin; Mustard, Cameron; Saunders, Ron; Scott‐Marshall, Heather
<x xml:space="preserve">Abstract</x> Background To examine if age differences in the consequences of work injury are exacerbated when occupational physical demands are higher. Methods A secondary analysis of workers' compensation claims in British Columbia (N = 373, 672). Regression models examined the relationship between age and health care expenditures, days of wage replacement and the occurrence of long‐term‐disability following a work‐related injury in occupations with lower and higher physical demands. Models were adjusted for individual and injury related covariates. Results Older age and higher occupational physical demands were associated with worse work‐injury outcomes. The relationship between age and each outcome was not exacerbated when occupational physical demands were higher compared to when they were lower. Counter to our hypotheses age differences in health care expenditures were smaller among women in more demanding occupations. Conclusions In this study, we found no evidence that the relationship between age and the consequences of work injury is exacerbated when physical occupational demands are high. Am. J. Ind. Med. 57:438–444, 2014. © 2014 Wiley Periodicals, Inc.